PERAN LEMBAGA INKUBATOR BISNIS TERHADAP PENGELOLAAN MANAJEMEN USAHA UMKM DI KABUPATEN PIDIE - Hasbi; Saiful Bahgia (JURNAL KREASI RAKYAT, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the regional economy, yet they frequently face challenges in managing their businesses. Business incubators offer a solution to enhance the managerial capacity of MSMEs through coaching and mentoring programs. This study aims to examine the role of business incubators in the management of MSMEs in Pidie Regency. This study employed a qualitative approach with descriptive methods. Data collection techniques included in-depth interviews with MSMEs assisted by the incubators, participant observation, and analysis of incubation program documents. Informants were selected purposively, focusing on MSMEs that had participated in the incubation program for at least six months. Findings indicate that business incubators play a role in three main aspects: financial management training, strengthening digital marketing, and facilitating networking and access to funding. Most MSMEs experienced increased business management capacity after participating in the incubation program, in terms of planning, financial records, and promotional strategies. The strategic role of business incubators has been proven to encourage the professionalization of MSMEs and increase the competitiveness of local businesses. However, the program's success still faces obstacles in terms of sustainable mentoring and limited reach. This study recommends the need for institutional strengthening policies and cross-sector collaboration to support a sustainable incubation ecosystem.